Périphérie et identité locale ? - Virginia Capote Díaz (Caravelle)
This essay aims to describe an overview of the independent publishing houses of Colombian literature. We will analyse the way in which the independent editorial market works as an alternative and resists to the publishing dynamics of the transnational companies. Therefore, we will focus on the values of violence, identity and genre.